Mapping the Country of Regions : The Chorographic Commission of Nineteenth-Century Colombia - Appelbaum, Nancy P. (Book collections on Project MUSE., 2016)
The 19th century was an era of breathtakingly ambitious geographic expeditions across the Americas. The seminal Chorographic Commission of Colombia, which began in 1850 and lasted about a decade, was one of Latin America's most extensive. The commission's mandate was to define and map the young republic and its resources with an eye toward modernization. In this history of the commission, Nancy P. Appelbaum focuses on the geographers' fieldwork practices and visual production as the men traversed the mountains, savannahs, and forests of more than 30 provinces in order to delineate the country's territorial and racial composition.